The Rights of the Jehovah’s Witnesses in Russia and Beyond: The Role of the European Court of Human Rights - Richardson, James T. (The journal of CESNUR, 2020)
This article briefly discusses the history of the Jehovah’s Witnesses, focusing on their early decisions to use legal systems to defend themselves and expand their rights to practice their faith. Their legal successes in the United States and Canada in establishing religious freedom rights are summarized before examining the role played in the expansion of religious freedom in Europe through cases won in the European Court of Human Rights. Witnesses cases have also expanded the purview and influence of the courts systems in various Western societies. ECtHR has taken on special meaning with dozens of cases filed recently against Russia. The Russian government, with the blessing of its court system, has dissolved all Witnesses organizations, confiscated millions of dollars in property, harassed innumerable Witnesses families, and incarcerated dozens of Witnesses for alleged violations of statutes dealing with extremism. How the ECtHR will deal with these recent cases will reveal much about the future of the Court, and of the Council of Europe, especially if Russia refuses to honor any decisions that are rendered against it.